2003
DOI: 10.1093/fampra/cmg304
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a name? An experimental study of patients’ views of the impact and function of a diagnosis

Abstract: Although much current prescriptive literature in general practice advocates the use of lay language in the consultation as a means to promote better doctor-patient partnerships, the issue of diagnosis is more complex than this. Patients attribute greater benefits to the use of medical labels for themselves and state that such medical labels are of greater benefit to the doctor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 5 publications
(2 reference statements)
4
50
0
Order By: Relevance
“…To simplify the questionnaire the number of items in each subscale were reduced to three based on published reliability data (18). In addition, the patients were asked to rate items reflecting trust in the doctor as this has been shown to be influenced by choice of term in previous research (9). All but two of these subscales have acceptable reliability scores.…”
Section: Part 2: Impact Of the The Term 'Heart Failure' Vs The Favourmentioning
confidence: 99%
See 1 more Smart Citation
“…To simplify the questionnaire the number of items in each subscale were reduced to three based on published reliability data (18). In addition, the patients were asked to rate items reflecting trust in the doctor as this has been shown to be influenced by choice of term in previous research (9). All but two of these subscales have acceptable reliability scores.…”
Section: Part 2: Impact Of the The Term 'Heart Failure' Vs The Favourmentioning
confidence: 99%
“…Recent research explored this dilemma and examined the ways in which the choice of a specific term can have an impact upon how patients perceive their problem. In particular, Ogden et al (9) carried out an experimental study of the impact of presenting patients with either a lay diagnosis (ie. Sore throat) or a medical diagnosis (ie.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians should consider the impact of previous exposure to lay or medical labels on patients' sense of urgency for care and perceptions of disease characteristics (Young et al, 2008), as well as the impact of their own choice of disease label during patient-physician communication. Patients reported preferring physicians' use of medical labels because it validated their illness and enhanced their views of their physician's professionalism (Ogden et al, 2003). Consistent with findings that lay labels are perceived as less severe, less representative of disease, and more prevalent (Young et al, 2008), patients also felt a physician's use of lay labels indicated that the disease was less worrisome and would subside quickly (Ogden et al, 2003).…”
Section: Discussionmentioning
confidence: 67%
“…Patients reported preferring physicians' use of medical labels because it validated their illness and enhanced their views of their physician's professionalism (Ogden et al, 2003). Consistent with findings that lay labels are perceived as less severe, less representative of disease, and more prevalent (Young et al, 2008), patients also felt a physician's use of lay labels indicated that the disease was less worrisome and would subside quickly (Ogden et al, 2003). Based on this growing body of work, physicians should also avoid instances where particular labels may be misinterpreted and as a result, undermine treatment (Bokhour and Kressin, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Patients will respond differently when their diagnosis is given as medical terminology compared to as lay language [12]. In one study, use of the term "tonsillitis" made the patient feel they were be taken seriously and this resulted in greater confidence in the doctor.…”
mentioning
confidence: 99%